Orthogonally polarized dual-wavelength operation at 898 and 904 nm with tunable power ratio in Nd:SA/Nd:LMA crystals - Chu Chu; Xinghua Yang; Shuang Wang; Changli Li; Yongliang Li (Scientific Reports)
Abstract A diode-pumped continuous-wave (CW) orthogonally polarized dual-wavelength (OPDW) Nd:SrAl12O19/Nd:LaMgAl11O19 (Nd:SA/Nd:LMA) laser at 898 and 904 nm with tunable power ratio on 4 F 3/2 → 4 I 9/2 quasi-three-level transition is demonstrated for the first time. The pump wavelength and the waist position of the pump beam were optimized to achieve high efficiency and balanced output powers of OPDW laser. The OPDW laser at 898 and 904 nm was obtained with the highest total output power of 6.59 W and the power ratio of 1:1. The highest total slope efficiency and total optical-to-optical conversion efficiency related to the absorbed pump power at 796.85 nm were 39.7% and 36.2%, respectively. The OPDW laser at 898 and 904 nm has important application prospects in fields such as biomedicine, scientific research, gas detection, and remote sensing technology.